2022
DOI: 10.1371/journal.pcbi.1009394
|View full text |Cite
|
Sign up to set email alerts
|

Dominating lengthscales of zebrafish collective behaviour

Abstract: Collective behaviour in living systems is observed across many scales, from bacteria to insects, to fish shoals. Zebrafish have emerged as a model system amenable to laboratory study. Here we report a three-dimensional study of the collective dynamics of fifty zebrafish. We observed the emergence of collective behaviour changing between ordered to randomised, upon adaptation to new environmental conditions. We quantify the spatial and temporal correlation functions of the fish and identify two length scales, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The value of α in Eq. 2 changes the relative proportion of the two, and we set its value to be 0.63, consistent with previous work [40]. In our discussion on the effect of the α value of the model is available in the, we conclude that the α = 0.63 fitted to our data provides convincing evidence for some effective inertia in the zebrafish system.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The value of α in Eq. 2 changes the relative proportion of the two, and we set its value to be 0.63, consistent with previous work [40]. In our discussion on the effect of the α value of the model is available in the, we conclude that the α = 0.63 fitted to our data provides convincing evidence for some effective inertia in the zebrafish system.…”
Section: Resultssupporting
confidence: 77%
“…We found that the col11a2 -/- zebrafish showed significantly reduced bending compared to the wildtype. Then, in a 3d swimming environment, we recovered the 3d trajectories of fish swimming alone ( N = 1) or swimming as a group ( N = 25) with a custom three view tracking apparatus [40, 53, 54]. Strikingly, a single mutant fish took a significantly longer time to change its orientation, and a group of col11a2 -/- zebrafish exhibited more ordered movement characterised by the polarization order parameter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the classic Vicsek model, “alignment” and “noise” have been two basic components to determine the phase transition of collective motile agents, including self-propelled particles, hard rods, , and filamentous active matters. As a parameter defining the persistence distance of a motile agent, the L p has been widely recognized to be inversely proportional to noise. Although several theoretical models investigated the influence of L p on collective motion, experimental validations are still limited significantly. Here, we systematically investigated the influence of L p -dependent orientational noise of MTs on their collective motion.…”
Section: Resultsmentioning
confidence: 99%